Examining the Effects of Tramadol, on the WADA Prohibited List, on Sports Performance - Cemre Acar Halıcı; Aysun Hacışevki (Gazi Medical Journal)
Tramadol, an opioid analgesic, was added to the World Anti-Doping Agency (WADA) Prohibited List in 2024. Tramadol has been widely used by athletes to manage sports-related pain. Its intensive use, particularly in certain sports, has raised suspicions that it is being used as a doping agent. The potential to impair sports performance, cognitive side effects, and abuse have been investigated in several studies. This study reviewed the literature on tramadol and its effects on sports performance and explained the WADA process. In reviewing the literature, although studies have shown that tramadol does not affect performance, the World Health Organization has banned its use in competition in light of studies showing its effect on performance.